(untitled) (Publicatio UEPG: Ciências Sociais Aplicadas, 2021)
This article presents a research on the importance of the relationship school, family, and community. It analises the role of the family as what forms the humn being through education. The main objective for this descriptive research is to reflect on family and community engagement on school and its educational process. This qualitative study starts with the phenomenological thinking on education and the damily as a element that pushes social development. The theoretical foundation was obtained by the revision of literature, and is attributed to a body of authors of correlated areas. By doing case study of a school in a underdeveloped community, we observed attempts of integration between school, family, and community. This study intends to motivate other discussions about the relationship between school, family, and community, as beneficial to the students, provinding them quality education towards citizenship and peace. Keywords: Education. Relationship. School. Family. Community.